2022
DOI: 10.1002/ijgo.14395
|View full text |Cite
|
Sign up to set email alerts
|

The social and economic impacts of cervical cancer on women and children in low‐ and middle‐income countries: A systematic review

Abstract: Background There is limited knowledge on the social and economic impacts of a diagnosis of cervical cancer on women and children in low‐ and middle‐income countries (LMICs). Objectives To determine the social and economic impacts associated with cervical cancer among women and children living in LMICs. Search strategy The MEDLINE, PsychInfo, CINAHL, Pais International, and CAB Global Health databases were systematically searched to retrieve studies up to June 2021. Selection criteria Studies were included if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…Одним із найтривожніших аспектів цієї динаміки є вплив на профілактичні заходи в галузі охорони здоров'я. Регулярне медичне обслуговування, таке як скринінг на рак, має вирішальне значення для виявлення та лікування хвороб на ранній стадії [10]. На жаль, стигма, пов'язана зі зловживанням психоактивними речовинами, може перешкоджати доступу цих людей до вищезазначених профілактичних заходів.…”
Section: оригінальні дослідженняunclassified
“…Одним із найтривожніших аспектів цієї динаміки є вплив на профілактичні заходи в галузі охорони здоров'я. Регулярне медичне обслуговування, таке як скринінг на рак, має вирішальне значення для виявлення та лікування хвороб на ранній стадії [10]. На жаль, стигма, пов'язана зі зловживанням психоактивними речовинами, може перешкоджати доступу цих людей до вищезазначених профілактичних заходів.…”
Section: оригінальні дослідженняunclassified
“…Of all participants, half were in the age group 31 to 50 years, and most (9) had lived with cervical cancer for two years. Four (4) were single, the other 4 were divorced, and most (10) were Christians. Regarding the level of education and employment, 10 had a primary education, and 8 were self-employed.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Cervical cancer patients experience various changes in their lives, including physical, psychological, social, and spiritual changes [8,9]. There is enormous socioeconomic impact experienced by these patients, including loss of body image, loss of femininity, loss of sexual functioning, loss of income, social discrimination, nancial distress, and work and employment challenges [10][11][12]. It, therefore, signi cantly affects the quality of life (QOL) of survivors, including physical and psychological sequelae, family distress, nancial burden, and disruptions to their social functioning and sexual life [13].…”
Section: Introductionmentioning
confidence: 99%
“…Dau et al reported in their 2022 systematic review that there are only two studies in lowand middle-income countries that quantify the direct and indirect costs of cervical cancer treatments [14][15][16] However, as they are limited to two countries, they provide a limited understanding of the global burden. The first study by Hailu et al in Ethiopia measured both direct costs such as consultation fees and indirect costs such as lost wages.…”
Section: Introductionmentioning
confidence: 99%